Labrador, aerial view of mountainous coastline with inlets between Ungava Bay and Nachvak Fjord - Forbes, Alexander, 1882-1965 (1931)
(Series 33) West-east flight from Ungava Bay to Nachvak. Camera facing left front to line of flight. Grayscale